Ethel [videorecording (DVD)] - Kennedy, Rory (Home Box Office, Inc., 2013)
'Ethel' celebrates the remarkable life of Ethel Kennedy, the wife of Robert F. Kennedy, through a treasure trove of revealing and little-known anecdotes from those who know her best: her family. This personal portrait contains Ethel's first extended interview in more than 20 years. An official selection at the 2012 Sundance Film Festival, the documentary highlights the remarkable life of the Kennedy matriarch, and the love story between Ethel, now 84, and her late husband.